SYMBOLIC IMAGES IN I. YUSUPOV'S POETRY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
It is well known that one of the genres of literature that has been around since ancient times is poetry. For this reason, in ancient times, the whole art of word art was understood as "poetry". Its rapid reach and sensitivity to the human heart must have been closely connected with human life from time immemorial. In particular, the figurative aspect of poetry plays an important role in arousing beautiful feelings in the human heart, giving it aesthetic pleasure.There are different ways of figurative expression in poetry. One of them is the method of creating a symbolic image, which has been used in fiction for a long time. In it, we see that the symbolic representation of the image of birds is widely used in folklore, in the examples of classical literature.